Optimal Incentives for Teams: Comment - Ishiguro, Shingo (American Economic Review, 2002)
In a recent publication in this journal, YeonKoo Che and Seung-Weon Yoo (2001) have derived important implications of optimal contracts for teams by considering repeated interactions among multiple agents. First, in Proposition 1 they have argued that in a static setting the optimal contract displays the feature of relative performance evaluation (henceforth, RPE), which means that the wage of an agent is decreased when his peer performs well. Second, they have shown that in a dynamic setting the optimal contract may be based on joint performance evaluation (henceforth, JPE), which means that the wage of an agent is increased when his peer performs well, even in the parameter range in which RPE is optimal in a static setting.